Contemporary African fashion - Gott, Edith Suzanne; Loughran, Kristyne (Bloomington : Indiana University Press, 2010)
African fashion is as diverse and dynamic as the continent and the people who live there. This book puts Africa at the intersection of world cultures and globalized identities, displaying the powerful creative force and impact of newly emerging styles. Richly illustrated with color photographs, this book showcases haute couture for the African continent.--[book cover]
The Ghanaian kaba: fashion that sustains culture / Suzanne Gott -- The visual city: tailors, creativity, and urban life in Dakar, Senegal / Joanna Grabski -- Secondhand clothing and fashion in Africa / Karen Tranberg Hansen -- Fashion, not weather: a rural primer of style / Elisabeth L. Cameron -- Contemporary wedding fashions in Lagos, Nigeria / Elisha P. Renne -- African fashion: design, identity, and history / Victoria L. Rovine -- Using the past to sculpt the costume of the future: an interview with Kandioura Coulibaly / Janet Goldner -- Interesting creativities: Oumou Sy's costumes in the Dakar landscape / Hudita Nura Mustafa -- From cemetery to runway: dress and identity in highland Madagascar / Rebecca L. Green -- La sape exposed! High fashion among lower-class Congolese youth: from colonial modernity to global cosmopolitanism / Didier Gondola -- Have cloth---will travel / Kristyne Loughran -- Dressing Somali (some assembly required) / Heather Marie Akou -- Translating African textiles into U.S. fashion design: Brenda Winstead and Damali Afrikan Wear / Leslie W. Rabine.
Includes bibliographical references.
Keywords: Fashion -- Africa